COVID-19 and International Food Assistance: Policy proposals to keep food flowing - Cardwell, Ryan (World Dev, 2020)
The COVID-19 pandemic is increasing the need for international food assistance, and disrupting the supply and delivery of food assistance. A series of unprecedented shocks is straining the capacity of food assistance organizations to reach vulnerable populations. We discuss how the COVID-19 pandemic is affecting the demand and the supply of international food assistance, and we propose three policy changes that can keep food flowing to those in need. First, donor countries can prioritize humanitarian spending in aid-allocation decisions. Second, governments can exempt food assistance from trade barriers that impede procurement (export restrictions) and delivery (import tariffs). Third, donor countries can allow flexibility for implementing agencies by untying food assistance from domestic procurement and shipping restrictions. All of these proposals are regulatory changes that can be made without requiring increased spending. These options are particularly relevant now because donor-country governments are entering economic recessions, and foreign aid budgets will be constrained.